2000
DOI: 10.2105/ajph.90.8.1218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traditional classroom and distance continuing education: a theory-driven evaluation of a vaccine-preventable diseases course

Abstract: OBJECTIVES: This study evaluated the effects of a major federal immunization continuing education course, delivered in both traditional classroom and satellite broadcast versions, on public health professionals' knowledge, agreement, self-efficacy, and adherence in practice to recommendations. METHODS: The study used a comparative time series design to determine whether the course influenced participants' knowledge, agreement, self-efficacy, and adherence in practice to general and polio-specific recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The nine comparative studies [12][13][14][15][16][17][18][19][20] further reinforced comparable learning outcomes for face-to-face and telelearning delivery formats. Of note, videoconferencing was the prominent tele-learning method utilised by the majority of the comparative studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nine comparative studies [12][13][14][15][16][17][18][19][20] further reinforced comparable learning outcomes for face-to-face and telelearning delivery formats. Of note, videoconferencing was the prominent tele-learning method utilised by the majority of the comparative studies.…”
Section: Resultsmentioning
confidence: 99%
“…Another comparative study 20 of a large national immunisation continuing education course for the public health workforce in the United States demonstrated comparable outcomes for classroom and distance (satellite broadcasted) trained participants. The study concluded that classroom and distance delivery methods have comparable outcomes in continuing education and can foster the implementation of practice guidelines and recommendations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant pre-to-post gains were demonstrated overall and by practice discipline in procedural knowledge, professional self-efficacy (a recognized surrogate for actual performance), 43-45 and case-based skills. Similar to outcomes from the pilot intensive course, GCs had the highest baseline scores on all measures, and post-course knowledge scores were significantly higher among GCs and MDs compared with APNs.…”
Section: Discussionmentioning
confidence: 99%
“…46 Previous studies have also shown that increased self-efficacy following training predicts behavior among health professionals. 47,48 …”
Section: Methodsmentioning
confidence: 99%